On biconservative hypersurfaces in 4-dimensional Riemannian space forms - Turgay, Nurettin Cenk; Upadhyay, Abhitosh (arXiv, 2017)
In this paper, we study biconservative hypersurfaces in $\mathbb S^{n}$ and $\mathbb H^{n}$. Further, we obtain complete explicit classification of biconservative hypersurfaces in $4$-dimensional Riemannian space form with exactly three distinct principal curvatures.

22 Pages
Keywords: Differential geometry of immersions (minimal, prescribed curvature, tight, etc.); Mathematics - Differential Geometry; biconservative hypersurfaces; null 2-type submanifolds; Differential Geometry (math.DG); Global submanifolds; FOS: Mathematics; Riemannian space forms; Mathematics; biharmonic submanifolds